Intrasexual Competition and Eating Restriction in Heterosexual and Homosexual Individuals - Li, Norman P. (2010)
Restrictive eating attitudes and behaviors have been hypothesized to be related to processes of intrasexual competition. According to this perspective, within-sex competition for status serves the adaptive purpose of attracting mates. As such, status competition salience may lead to concerns of mating desirability. For heterosexual women and gay men, such concerns revolve around appearing youthful and thus, thinner. Following this logic, we examined how exposure to high-status and competitive (but not thin or highly attractive) same-sex individuals would influence body image and eating attitudes in heterosexual and in gay/lesbian individuals. Results indicated that for heterosexuals, intrasexual competition cues led to greater body image dissatisfaction and more restrictive eating attitudes for women, but not for men. In contrast, for homosexual individuals, intrasexual competition cues led to worse body image and eating attitudes for gay men, but not for lesbian women. These findings support the idea that the ultimate explanation for eating disorders is related to intrasexual competition.